Introduction to the Special Issue on Interactions Between Analytic and Islamic Philosophy/Theology - Abbas Ahsan; Marzuqa Karima (European Journal of Analytic Philosophy, 2022)
This article is an introduction to the special issue on interactions between analytic and Islamic philosophy/theology. Islamic philosophy and theology have historically demonstrated the aptitude and scope in being able to engage with philosophical rationalist traditions beyond classical Islamic civilisation. Articles in this special issue of the European Journal of Analytic Philosophy provide a new and fresh outlook of the relation and influences between Islamic philosophical and theological traditions and the Western (analytic) philosophical tradition.